2022
DOI: 10.1073/pnas.2200757119
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated blockade of the IL23 receptor destabilizes intratumoral regulatory T cells and enhances immunotherapy

Abstract: Significance Regulatory T cells rely on active processes to maintain a suppressive phenotype inside a tumor, leading to increased tumor burden and worse cancer outcomes. Here, we report a pathway to interfere with regulatory T cell (Treg) stability by disrupting the expression of the interleukin 23 receptor. This approach increases Treg responsiveness to interleukin 12, leading to increased production of gamma-interferon and more efficient antitumor immune responses. The combined engagement of indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 33 publications
2
16
1
Order By: Relevance
“…TLR2 typically responds to lipid-containing immunogens, while TLR4 typically responds to carbohydrate-derived immunogens. This is further supported by previous reports that TLR2 can respond to cardiolipin self-immunogens released by damaged mitochondria. , …”
supporting
confidence: 88%
See 1 more Smart Citation
“…TLR2 typically responds to lipid-containing immunogens, while TLR4 typically responds to carbohydrate-derived immunogens. This is further supported by previous reports that TLR2 can respond to cardiolipin self-immunogens released by damaged mitochondria. , …”
supporting
confidence: 88%
“…This is further supported by previous reports that TLR2 can respond to cardiolipin selfimmunogens released by damaged mitochondria. 20,21 Signaling through the TLR2 receptor typically requires a heterodimer of TLR2−TLR6 or TLR2−TLR1. 22−25 We used CRISPR/C as knockdowns in human monocytes to distinguish these possibilities (Figure 4).…”
mentioning
confidence: 99%
“…Direct inhibition of CTLs by IL-6 is mechanistically distinct from other cytokine-dependent processes that can potentially inhibit ICI efficacy, including recruitment of inhibitory myeloid cells by VEGF, 56 IL-1β, 57 IL-8, 58 , 59 or LIF, 60 suppression of tumor CTL infiltration by TGFβ, 61 and support of Treg function by IL-23. 62 , 63 Importantly, therapies targeting IL-6 and IL6R are approved for several conditions including rheumatoid arthritis, cytokine release syndrome, giant cell arteritis, and multicentric Castleman disease. 64 Given the extensive clinical experience with IL-6 inhibitors, and the pressing need to improve upon existing immunotherapies, combination of ICIs with approved anti-IL-6/IL6R agents warrants investigation in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, identifying IL-23R-expressing cells has been challenging due to the poor specificity of available antibodies and low expression of IL-23R. Nevertheless, two reports have suggested that T reg cells express IL-23R in preclinical models of cancer 14 , 22 . By generating an IL-23R reporter mouse, we demonstrated IL-23R expression in T reg cells in the TME.…”
Section: Discussionmentioning
confidence: 99%